2017
DOI: 10.1007/s10230-017-0491-z
|View full text |Cite
|
Sign up to set email alerts
|

International Trials of Vertical Flow Reactors for Coal Mine Water Treatment

Abstract: previous research confirmed that VFRs can be used as standalone passive treatment systems for iron removal from mine waters with a footprint less than half of the area required by a conventional aerobic wetland. A VFR can also provide useful iron pretreatment for other passive treatment systems under circumneutral conditions, but would have to be combined with alkaline generating systems to achieve full iron removal from acidic mine waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, it was found that 107-640 g of limestone is required to neutralize 1 L of AMD, making the application of neutralization quite expensive and unsafe when treating large amounts of AMD produced in coal mines [11]. The use of constructed wetlands (CWs) for AMD treatment is a rapidly developing passive treatment technology that focuses mainly on metal and sulfate removal [12,13]. CW is Sustainability 2022, 14, 2148 2 of 13 a substrate-microbial-plant composite ecosystem with physical, chemical, and biological triple synergy [14], which is an economic, efficient, and environment-friendly AMD remediation technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that 107-640 g of limestone is required to neutralize 1 L of AMD, making the application of neutralization quite expensive and unsafe when treating large amounts of AMD produced in coal mines [11]. The use of constructed wetlands (CWs) for AMD treatment is a rapidly developing passive treatment technology that focuses mainly on metal and sulfate removal [12,13]. CW is Sustainability 2022, 14, 2148 2 of 13 a substrate-microbial-plant composite ecosystem with physical, chemical, and biological triple synergy [14], which is an economic, efficient, and environment-friendly AMD remediation technology.…”
Section: Introductionmentioning
confidence: 99%